PERJANJIAN ELEKTRONIK PADA PEDULILINDUNGI YANG BERTRANSFORMASI MENJADI SATUSEHAT BERDASARKAN HUKUM NASIONAL TERKAIT - Faradila Khairunisa (JOURNAL OF LAW AND NATION, 2024)
This research focuses on understanding the legal protection of electronic agreements based on relevant national laws and reviewing the legal consequences of electronic agreements on the transformation of the PeduliLindungi application into the SATUSEHAT application. This research uses a normative juridical legal research method that focuses on reviewing literature sourced from laws and regulations, books, journals, and other documents. The analysis technique used in this research is descriptive. Electronic agreements are regulated in Law Number 11 of 2008 concerning Electronic Information and Transactions and Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions as implementing regulations of Law Number 11 of 2008 concerning Electronic Information and Transactions. Electronic agreements on the PeduliLindungi application arise prior to the use of the application by users in the form of terms and conditions of application services. These terms and conditions must meet the legal requirements of the agreement, because any agreement in conventional or electronic form is subject to the rules in Book III of the Civil Code.The transformation of the PeduliLindungi application into the SATUSEHAT application is a government action that is not in accordance with the terms and conditions of application services, resulting in legal consequences in the form of default in the form of doing something that is not promised in the agreement